2022
DOI: 10.1007/s10439-022-03087-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rotated Head Postures on Volunteer Kinematics and Muscle Activity in Braking Scenarios Performed on a Driving Simulator

Abstract: Occupants exposed to low or moderate crash events can already suffer from whiplash-associated disorders leading to severe and long-lasting symptoms. However, the underlying injury mechanisms and the role of muscle activity are not fully clear. Potential increases in injury risk of non-nominal postures, i.e., rotated head, cannot be evaluated in detail due to the lack of experimental data. Examining changes in neck muscle activity to hold and stabilize the head in a rotated position during pre-crash scenarios m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…While the safety system dramatically reduced the impact of the head, the differences in peak head acceleration between the different types of models were larger than the differences due to anthropometry alone. Since the risk of injury can also vary with posture in the pre‐crash phase [55], our second case study focused on tuning a head‐neck reflex controller specifically [56] and simulating pre‐crash scenarios in general. In both cases, these tasks required multibody models, such as Madymo [36], as the cost of performing thousands of finite element simulations would have been prohibitive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the safety system dramatically reduced the impact of the head, the differences in peak head acceleration between the different types of models were larger than the differences due to anthropometry alone. Since the risk of injury can also vary with posture in the pre‐crash phase [55], our second case study focused on tuning a head‐neck reflex controller specifically [56] and simulating pre‐crash scenarios in general. In both cases, these tasks required multibody models, such as Madymo [36], as the cost of performing thousands of finite element simulations would have been prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…In a volunteer test study approved by the local ethical committee, the behavior of 17 typical participants was investigated during a mixed reality braking scenario. The participants were asked to look ahead (nom), or to the right (sho) (see photos in Figure 18A), so that their movements and muscle activity could be studied [53,56]. As in other volunteer studies, a large variability in the volunteers' behavior can be observed (Figure 18A,B).…”
Section: Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…The passive properties of the AHBM have been validated using PMHS tests [113]. Many active properties of the model have been indirectly validated by comparing the response of the entire head and neck model to in-vivo sled tests [9,14,56], Driver-in-the-Loop (DiL) tests [20,51,53], and tests in real vehicles [42,91]. An overview of available tests is provided by the OSCCAR consortium [88].…”
Section: Simcenter Madymomentioning
confidence: 99%
“…DiL test allows to put the occupant into new (virtually) interior concepts while exposed to a mixed-reality scenario and to study the interaction under (limited) external loading. Different test series, see [50,53,20] were performed to gain a better understanding of human behavior in such situations. To analyze the driver's behavior in experiments, the kinematics and muscle activation are monitored, see Fig.…”
Section: Case Study -Madymo Ahbm In a Driver-in-the-loop Simulator An...mentioning
confidence: 99%